Geometryczne sumy losowe - Malinowski, Marek
This PhD thesis concerns two issues connected by idea of geometrie random sums: the first issue is a Dugue's problem, the second issue is a problem of characterizations of geometrie infinitely divisible distributions and some of their subclasses. The Dugue's problem relies on characterizing of distributions !.l, v for which their convex combination is equal to their convolution. We obtained a theorem which allows us to treat Dugue's problem in terms of the simple fractions class of characteristic function.
Keywords: problem Dugue; rozkłady geometrycznie nieskończonie podzielne; rozkłady geometrycznie semistabilne